From digital learning to artificial intelligence: Enhancing autonomy among students of Islamic education - Deddy Ramdhani; Hakiman Hakiman (UIN Raden Mas Said Surakarta, 2025)
The digitalization of education has significantly broadened access to diverse learning resources, including Artificial Intelligence (AI)-powered tools, thereby offering new avenues for students to cultivate greater autonomy in their learning. This study investigates the level of learner autonomy, the contributing factors, and the potential of AI in supporting autonomous learning among undergraduate students of Islamic Religious Education in the digital learning era. Employing an explanatory mixed-methods design, the research integrates quantitative and qualitative approaches. Quantitative data were collected through a structured questionnaire distributed to 103 students and analyzed using descriptive statistics, while qualitative insights were obtained through semi-structured interviews with four participants. Quantitative findings reveal a high overall level of learner autonomy (mean = 3.66), particularly in students’ ability to access learning materials independently (mean = 4.07), utilize digital resources effectively (mean = 4.02), and select appropriate learning strategies (mean = 3.91). However, limitations persist in students’ reliance on lecturers for digital resource utilization (mean = 2.92) and moderate digital proficiency (mean = 3.56). Key contributing factors include the accessibility of digital learning resources (mean = 3.96) and lecturer guidance (mean = 3.76). Qualitative results highlight the promising potential of AI tools, such as chatbots, intelligent tutoring systems, and adaptive learning platforms, in providing personalized support, instant feedback, and motivation for independent learning. These findings underscore the importance of integrating AI technologies and tailored instructional strategies to foster learner autonomy. The study offers empirical evidence to inform curriculum development and policy initiatives that strengthen self-directed learning in Islamic higher education.